If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6-(2x-8)=4-3x
We simplify the equation to the form, which is simple to understand
6-(2x-8)=4-3x
Remove unnecessary parentheses
6-2x+8=4-3x
We move all terms containing x to the left and all other terms to the right.
-2x+3x=+4-6-8
We simplify left and right side of the equation.
+1x=-10
We divide both sides of the equation by 1 to get x.
x=-10
| 14-3x=x+2 | | 14=7x-2x+9 | | x+x-150=180 | | -16+-10x=7x+18 | | 7-(4x-2)=8-5x | | 5+x-5x=-11 | | x+x/5=180 | | 15x+5x=6x | | 9(w-4)=8(7+w) | | 5.25Z-2.01=-8.94 | | 22+65=4+25 | | -34+3x=14-3x | | -8(x-8)-5=59 | | 8=-3x+2 | | 7(x-3)=7+6x | | 2x-6-3x=2 | | 15-.75g=13-50g | | e^3x+1=20 | | x-.10x=18.00 | | -3x+x^3=0 | | 76=(2x-6)3 | | 14+2p=20+15 | | 5x-9=6x-2 | | 7(y+2)=7y+14 | | 17=(-x-4)2 | | 9+9x=41-x | | 9-5x-7x=-135 | | 16000(x+.005)-15000x=145 | | -9(-1-3x)=80 | | -3/4/1/2 | | 6x+29=5x+3 | | -2x-31=6x+17 |